The First Implementation of Land Consolidation for Paddy Fields in Indonesia Distributed in Sukamulya and Rancajawat, Tukdana Sub-district of Indramayu District of West Java in the Rentang Irrigation Modernization Project - Tatsuhiko Hiraiwa; K. Hady Susanto; Edwin Mardiansa; Maria Christina Kurniawati; Taofik Arif Hidayat; Yoshiharu Minoura; Takashi Hiruta; Muhammad Daffa Al Farras (Indonesian Soil Science Society of South Sumatra in Collaboration With Soil Science Department, Sriwijaya University, 2025)
The agriculture sector in Indonesia contributes 14.5% share of gross domestic product (GDP) in 2012 and the number of farmer accounts for about 40% of total labor force population in Indonesia. However, many of the irrigation systems have seriously been deteriorated. Consequently, DGWR (Director General of Water Resources) cannot operate the irrigation systems properly and the farmers have been facing difficulties in obtaining sufficient irrigation water and rice production. Based on the results of “appraisal mission for Rentang Irrigation Modernization Project between Japan International Cooperation Agency (JICA) and Government of Indonesia Represented by Ministry of Public Works and Housing and National Development Planning Agency” (August 2016), the Rentang Irrigation Modernization Project (hereinafter called RIMP) was started in August 2020. The RIMP consists of 15 packages for canal upgrading works, one (1) package for TM/TC system works, and one (1) package for Modernization Support Program (hereinafter called MSP). This paper mentions the land consolidation which is one of important and advanced activities in the RIMP, including background of the first introduction in Indonesia, site selection, socialization with benefit farmers, survey including geographical and cadastral and agricultural soil, design of irrigation canals and drains and farm roads, a land reallocation plan, issue of land certifications, improvement of soil, coordination with farmers during construction, introduction of IPHA (Water Efficient Rice Irrigation) and mechanization, and a knowledge movie. The implementation resulted in about a 90% increase in plot size and notable improvement in irrigation efficiency.